Regional economic impact of fishing and hunting in Finland - Urszula Zimoch; Hannu Törmä; Jouko Kinnunen; Mikko Rautiainen (European Regional Science Association (ERSA), 2014)
Regional economic impacts of fishing and hunting in Finland A state enterprise, Metsähallitus, administers state-owned land and water areas in Finland covering approximately 12 million hectares. One of the official administrative duties of Metsähallitus is to provide hunting and fishing opportunities for citizens. In 2013, more than 81,000 hunting licenses and 71,000 fishing licenses were granted. As indicated in the study, during one season, Metsähallitus hunting and fishing customers spent over EUR 33 million in the regions of licenses destinations. This paper indicates that hunters and fishers in Finland travel extensively and support the regional economy via their expenditures. In the summer and autumn of 2013, Metsähallitus carried out a survey that provided rich and up-to-date information that could be used for quantitative and qualitative research. For modelling purposes the private expenditures of hunters and fishers were grouped into trade, accommodation, restaurants, local public transport, and entertainment. However, the study also analysed these expenditures in more detail, presenting the personal expenditures per trip, per day of a trip, and per license. Moreover, the location of the expenditures was disaggregated into the region of license destination, the region of residence, and "on the way" between those two. For example, an average grouse hunter with a short-time (1?7 days) license in 2013 spent around EUR 150 per hunting trip within his or her region of residence, and more than EUR 440 per trip if the hunting area was located outside the region of residence. RegFin, a comparative-static regional Computable General Equilibrium (CGE) model was used in this study to calculate the wider economic impacts at a regional level, as well as to serve as an engine for an Excel-based assessment tool. The assessment of the regional economic impacts focused on basic economic indicators such as regional gross domestic product (GDP), household consumption, and employment. The results of the study indicate that hunting and fishing activities have a positive impact on regional economies. Just considering license destination regions in 2013, hunting and fishing on state-owned land increased regional GDP by EUR 6.4 million, created 86.2 person working years, and produced household consumption of EUR 36.6 million. Among the many conclusions, it was found that investments in regional services linked to hunting and fishing activities would increase the regional economic impacts of Metsähallitus customers.
Keywords: R13; C68; Q57; 330